PYK2 is overexpressed in chronic lymphocytic leukaemia: A potential new therapeutic target. Issue 4 (6th February 2023) - Sbrana, Francesca Vittoria; Fiordi, Benedetta; Bordini, Jessica; Belloni, Daniela; Barbaglio, Federica; Russo, Luca; Scarfò, Lydia; Ghia, Paolo; Scielzo, Cristina
Abstract: Chronic Lymphocytic Leukaemia (CLL) is the most common adult B‐cell leukaemia and despite improvement in patients' outcome, following the use of targeted therapies, it remains incurable. CLL supportive microenvironment plays a key role in both CLL progression and drug resistance through signals that can be sensed by the main components of the focal adhesion complex, such as FAK and PYK2 kinases. Dysregulations of both kinases have been observed in several metastatic cancers, but their role in haematological malignancies is still poorly defined. We characterized FAK and PYK2 expression and observed that PYK2 expression is higher in leukaemic B cells and its overexpression significantly correlates with their malignant transformation. When targeting both FAK and PYK2 with the specific inhibitor defactinib, we observed a dose–response effect on CLL cells viability and survival. In vivo treatment of a CLL mouse model showed a decrease of the leukaemic clone in all the lymphoid organs along with a significant reduction of macrophages and of the spleen weight and size. Our results first define a possible prognostic value for PYK2 in CLL, and show that both FAK and PYK2 might become putative targets for both CLL and its microenvironment (e.g. macrophages), thus paving the way to an innovative therapeutic strategy.